Research on Logistics Distribution Vehicle Scheduling Based on Heuristic Genetic Algorithm. (30th August 2021) - Wang, Chun-Li; Wang, Yang; Zeng, Ze-Yu; Lin, Cheng-Yu; Yu, Qiu-Li
Abstract : To study the genetic algorithm, this paper solves the problem of shop scheduling under the premise of layout Flying − V . Firstly, double-layer coding is used for optimization. When calculating fitness, the time to return to the mouth P & D approaches the optimum through the greedy idea. Individual screening is carried out through the roulette method. Different crossover and genetic operators are used for different coding layers. Through thinking of elitism and catastrophe and the immigration operator to ensure the diversity of the algorithm in the calculation process, it can achieve the recommendation of the number of cars to control the cost. The stability of the algorithm is good. It can recommend a better picking sequence and number of carts for various types of picking problems.